(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the study of the methods of word formation in English and Uzbek, and especially the method of abbreviation. Also, research is conducted on the difficulties and differences encountered in the use of this abbreviation method in English and Uzbek languages. In this article, the importance level of words created using the abbreviation method in various aspects of social field is explained, along with the important characteristics of expressing the language more clearly in that field. Furthermore, the article discusses the importance level of abbreviation in the current language as a method of expressing widely used languages, as well as aspects that set it apart from other methods of expression in oral communication. Additionally, various opinions and observations of different scholars about the importance level of abbreviation method are discussed. In the conclusion of the article, it is highlighted how abbreviation method can move forward in terms of importance level, its potential to develop as a new way of creating words, or alternatively, to expand our language as a new method is illustrated.